Pengaruh Dukungan Keluarga Dan Pelayanan Petugas Fasilitas Kesehatan Terhadap Status Imunisasi Dasar Lengkap pada Baduta Puskesmas Ponorogo Utara di Masa Pandemi Covid-19 - puspa, andini bhuana (Tadulako University, 2022)
PD3I is an infectious disease that has the potential to cause outbreaks and death, especially in toddlers. The number of PD31 cases each year always varies. In 2020, only 3 out of 10 villages managed to achieve the 93% target of the Ponorogo District Health Office. (4). Immunization failure is also exacerbated by entering the Ponorogo area with the orange zone along with 21 districts/cities in East Java. This study aims to determine the effect of family support and the services of health facility workers on the complete basic immunization status of under-fives during the Covid-19 pandemic. This study uses quantitative research methods with a case control approach. Data analysis in this study used the Chi Square test and 95% Confidence Interval (CI) and Odd Ratio (OR) which was intended to be able to see the influence between the independent variables on the dependent variable. The research was conducted on under-aged women in the working area of ​​the North Ponorogo Public Health Center, Ponorogo Regency with a total sample of 70 people. The results show that the service of health facility workers on the complete basic immunization status in under-fives during the Covid-19 pandemic is not related (p = 1, OR = 1) . Family support for complete basic immunization status in under-fives during the Covid-19 pandemic was related (p=0.000, OR=12.08). The conclusion of the study is that family support has an influence and is related, while the service of officers is not related and has no effect Keywords : Baby under two, Family Support, Completed Basic Immunization, Service of Health Facility